2020
DOI: 10.1111/mmi.14648
|View full text |Cite
|
Sign up to set email alerts
|

Activity, delivery, and diversity of Type VI secretion effectors

Abstract: The bacterial type VI secretion system (T6SS) system is a contractile secretion apparatus that delivers proteins to neighboring bacterial or eukaryotic cells. Antibacterial effectors are mostly toxins that inhibit the growth of other species and help to dominate the niche. A broad variety of these toxins cause cell lysis of the prey cell by How to cite this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 119 publications
(299 reference statements)
2
118
0
Order By: Relevance
“…VgrG and PAAR are found in large numbers in both orphan and main operons, suggesting no bias (Figure 4B). Since T6Es act generally as antibacterial toxins (Jurėnas and Journet 2021), the identity of the C-terminal domains of "evolved" T6SS cores are of high interest to science and industry. We surveyed all pfam domains encoded in C-terminal domains of HCP, VgrG, and PAAR.…”
Section: T6ss-encoding Bacteria Live a Pathogenic Lifestyle And Are Enriched In Specific Tissues Of Humans And Plantsmentioning
confidence: 99%
“…VgrG and PAAR are found in large numbers in both orphan and main operons, suggesting no bias (Figure 4B). Since T6Es act generally as antibacterial toxins (Jurėnas and Journet 2021), the identity of the C-terminal domains of "evolved" T6SS cores are of high interest to science and industry. We surveyed all pfam domains encoded in C-terminal domains of HCP, VgrG, and PAAR.…”
Section: T6ss-encoding Bacteria Live a Pathogenic Lifestyle And Are Enriched In Specific Tissues Of Humans And Plantsmentioning
confidence: 99%
“…Using the fully resolved organismal phylogeny as a framework, next we examined the molecular evolution of their T6SS genes. The T6SS is a phage tail-like contractile nanomachine for injecting effectors (i.e., toxins) into eukaryotic or bacterial cells, and plays a major role in pathogenesis, symbiosis, or interbacterial competition (33,34). For A. tumefaciens, the T6SS is a key weapon for in planta competition between different genomospecies (27) and against other bacteria (30).…”
Section: The Type VI Secretion System (T6ss) Genesmentioning
confidence: 99%
“…We first focus on genes encoding the T6SS, a phage tail-like contractile nanomachine commonly found in Proteobacteria and used to inject effectors into eukaryotic or bacterial cells. The T6SS has major roles in pathogenesis, symbiosis, and interbacterial competition [30][31][32][33]. For A. tumefaciens, the T6SS is a key weapon for in planta competition between different genomospecies [7] and against other bacteria [27].…”
Section: Diversity and Evolution Of The T6ss Genesmentioning
confidence: 99%
“…The chromosomal regions encoding Rhs repeats were originally described in Escherichia coli genomes as sites where recombination frequently took place 17 . Later studies revealed that Rhs repeat-containing proteins are not unique to E. coli but are common across Proteobacteria 18, 19 . Other more distant homologs, called teneurins, are involved in axon guidance in vertebrates 20–22 .…”
Section: Introductionmentioning
confidence: 99%